A 2,326-year tree-ring record of climate variability on the northeastern Qinghai-Tibetan Plateau - Zhang, Qi-Bin; Cheng, Guodong; Yao, Tandong; Kang, Xingcheng; Huang, Jianguo (Geophysical research letters, 2003)
High‐resolution climate proxy records covering the last two millennia on the Qinghai‐Tibetan Plateau are scarce yet essential to evaluation of the patterns, synchroneity and spatial extent of past climatic changes including those in the Medieval Warm Period (MWP) and the Little Ice Age (LIA). Here we present a 2326‐year tree‐ring chronology of Sabina przewalskii Kom. for Dulan area of northeastern Qinghai‐Tibetan Plateau. We find that the annual growth rings mainly reflect variations in regional spring precipitation. The greatest change in spring precipitation during the last two millennia seems to occur in the second half of the 4th century. The North Atlantic MWP was accompanied by notable wet springs in the study region during A.D. 929–1031 with the peak occurring around A.D. 974. Three intervals of dry springs occurred in the period of LIA. Our tree‐ring data will facilitate intercontinental comparisons of large‐scale synoptic climate variability for the last two millennia.